A constituição de ações intersetoriais de atenção às crianças e adolescentes em sofrimento psíquico - Taño, Bruna Lídia (Universidade Federal de São Carlos, 2017)
Moving forward in the discussion about the ways in which are produced intersectoral actions between mental health (specifically Psychosocial Care Centers for Children and Adolescents - CAPSij) and school can contribute to a better outline of public policies for education and health. The objectives of this research were to identify and understand the challenges and potentialities of intersectoral work within the interface of the fields of child and adolescent mental health and education; to identify how intersectoral work has been produced in the CAPSij of the southeastern region of Brazil and to perform/mediate an experience of promoting intersectoral practices among mental health services for children and adolescents and education. Therefore, the research adopted as methodological design the Triangulation of Methods Evaluation as an approach for the evaluation of social programs, outlining in two complementary studies. In the Study I, of quantitative approach, were identified the main intersectoral actions in which the CAPSij of the southeastern region of Brazil were involved. For this, 35 services participated through a questionnaire filling, answered by managers/coordinators. The data were analyzed descriptively and allowed identifying that the main benefits of intersectoral work are joint responsibility, guarantee of care integrality and qualification of work, revealing that the intersectoriality as exercise and guideline presents positive points for all the subjects involved: workers, children, adolescents and families. On the other hand, the main challenges and difficulties point out to the rigidity of certain services, the impediments to the implementation of pacts and the culture of pathologization/medicalization in society, and specifically, in the school environment. Regarding the children and adolescents followed by this study, the results show significant numbers of them passing through an exclusion situation in school. Among the main reasons for it, were highlighted situations that individualize the problematic, such as severity of the case, family aspects and vulnerability conditions. Families and communities, due to the presented results, are little considered in intersectoral actions/pacts. The Study II, of a qualitative approach, developed through action research, sought to understand about the production of intersectoral networks between mental health services for children and adolescents and education. The study was conducted in the city of Rio Claro-SP and was constituted by different movements that sought the collective construction of a common project among the sectors, counting with the participation of managers and workers from education, the CAPSij and the mental health clinic for children and adolescents. The results allowed clarifying that the concepts of territory and extended clinic are fundamental to the execution of intersectoral practices and that they must first be part of the work programs of each institution. Regarding the research with schools, the study allowed arguing that the lack of public policies on education/mental health and, even more, the absence of more dialogical debates and articulations, produces a discursive silencing that results in lack of attendance to students. In this sense, the practice of horizontal articulation through the implementation of an Intersectoral Pilot Project guaranteed the possibility of dialogue and partnership. The results and discussion allowed considering the intersectoriality as a horizon, since it is procedural and calls for psychosocial attention to be imbued with the task of sustaining the creation of broader discursive fields that act on more shared actions collectively.
Keywords: Saúde mental; Criança; Adolescente; Serviços de saúde mental; Educação inclusiva; Intersetorialidade; Mental health; Child; Adolescent; Mental health services; Inclusive education; Intersectoriality; CIENCIAS HUMANAS::EDUCACAO